ANALISIS FINANSIAL BIOGAS LIMBAH CAIR KELAPA SAWIT SEBAGAI ENERGI TERBARUKAN DI PKS RAMBUTAN PTPN III (FINANCIAL ANALYSIS OF PALM OIL BIOGASS FROM MILL EFFLUENT OF CRUDE PALM OIL FACTORY AS A RENEWABLE ENERGY IN PKS RAMBUTAN PTPN III) - M. Afif Shahputra (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2017)
Currently, development and investment policies can not be separated from environmental conservation efforts. Research is conducted through observation of biogas production from palm oil mill waste to generate electricity. This is not only beneficial for conservation efforts, but also for economic gain. The research was conducted at the division of Rambutan plantation in PTPN III. The purpose of this study is to conduct a financial investment analysis to ensure investors developing biogas installation of biogas electricity generators. Before technical analysis firstly we analyse potential electricity market then conducted technical development feasibility analysis. Then we conducted economic analysis includes investment feasibility criteria including Net Present Value (NPV) Net Benefit Cost, Payback Period (PBP) and sensitivity analysis. The results show that the construction of biogas plant oil palm waste plant is very feasible to do with a plant with a capacity of 45 tons / hour could produce 1 MWh of electricity. Keywords: palm oil mill effluent, biogas, financial analysis, NPV, BC ratio, sensitivity analysis